PENGARUH PERBANDINGAN SOSIAL TERHADAP SUBJECTIVE WELL- BEING PADA PENGGUNA AKTIF INSTAGRAM DI KOTA BANDUNG - Dewi Fortuna, - (2023)
This research is conducted to determine the effect of social comparison to subjective well-being in active instagram users at Bandung City. Researcher use quantitative method with correlational design. This research was conducted on 411 active Instagram user respondents in Bandung City with age range 19 to 34 years old. Research data was collected by filling out the Iowa-Netherlands Comparison Orientation Measure, Satisfaction with Life Scale (SWLS), and Scale of Positive and Negative Experience (SPANE) questionnaires. The sampling technique uses non-probability sampling with convenience sampling type and data collection is done by distributing online questionnaires via Google Forms. Data analysis techniques using simple regression test. The result of this study showing there is an influence between social comparison and subjective well-being in active instagram user at Bandung City.